Changes in the German Urban System—A Financial-Sector Perspective - Klagge, Britta; Peter, Carsten (Raumforschung und Raumordnung | Spatial Research and Planning, 2011)
Urban systems analysis and especially the seminal contributions of the Globalization and World Cities Research Network (GaWC) so far mainly rely on the analysis of national and international office geographies of advanced producer services firms. This paper shows how the geography of demand-supply relationships and associated knowledge flows adds important qualitative information to the office geographies of the Globalization and World Cities Research Network. It contributes to our understanding of intercity relations and networks—and thus of urban systems more generally. We illustrate our approach by looking at private equity firms and their knowledge management strategies in Germany. Empirically, we analyze private equity firms’ business relations and networks with external partners as well as their geographical organization. While private equity firms’ geographical organization in Germany is characterized by decentralized concentration with nodes in Frankfurt and regional financial centres, there is evidence that among the latter Munich plays a special role. Only in Munich has private equity—cross-fertilized by other local financial actors—initiated a self-supporting development which strengthens Munich as a financial centre. The paper illustrates how the dynamics of private equity and its knowledge management lead to Germany’s financial system having a more tiered structure and how qualitative network analysis can help deepen our understanding of urban systems development.
Keywords: Urban system; Financial centre; Financial sector; Private equity; Knowledge management; Network analysis; Germany